2017
DOI: 10.3892/mmr.2017.7210
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1291 promotes endometrial fibrosis by regulating the ArhGAP29-RhoA/ROCK1 signaling pathway in a murine model

Abstract: Intrauterine adhesions (IUAs) are caused by endometrial damage and are associated with a poor pregnancy prognosis including infertility, oligomenorrhea and recurrent pregnancy loss. Understanding the pathogenesis of IUAs may help prevent and treat this condition more effectively. The aim of the current study was to investigate the function of microRNA-1291 (miR-1291) during the development of IUAs following endometrial damage and elucidate the potential molecular mechanisms involved. The expression of Rho GTPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 32 publications
0
31
0
2
Order By: Relevance
“…Mice with reduced ARHGAP29 protein expression levels die perinatally with signs of abnormal cranofacial, limb and skin morphogenesis (Biggs et al, 2014) and a ARHGAP29 knockout in epiblast cells results in embryonic death at midgestation (Barry et al, 2016). Furthermore, reduced expression of ARHGAP29 has been correlated with cancer metastasis (Qiao et al, 2017) and endometrial fibrosis (Xu et al, 2017). These data indicate that ARHGAP29 levels need to be tightly controlled to ensure accurate embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with reduced ARHGAP29 protein expression levels die perinatally with signs of abnormal cranofacial, limb and skin morphogenesis (Biggs et al, 2014) and a ARHGAP29 knockout in epiblast cells results in embryonic death at midgestation (Barry et al, 2016). Furthermore, reduced expression of ARHGAP29 has been correlated with cancer metastasis (Qiao et al, 2017) and endometrial fibrosis (Xu et al, 2017). These data indicate that ARHGAP29 levels need to be tightly controlled to ensure accurate embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified miR-21, miR-27, miR-96, miR-128, miR-155 and miR-182 as oncogenes, and miR-17, miR-27, miR-125, miR-145, miR-205 and miR-206 as tumor suppressor genes [ 13 - 15 ]. Several miRNAs have been identified in normal endometrial tissues [ 16 , 17 ], but the possible involvement of miRNAs expression in endometrial cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies suggested in the literature for the formation of IUA and AS models, endometrial trauma was attempted to create by using 24 G [18] or 27 G [16,19,20] needles. In those studies, the abdomen was opened surgically, the uterine horns were reached and trauma was created by entering the lumen with a needle.…”
Section: Discussionmentioning
confidence: 99%